Temporal characteristics of the pulsed electric discharges in small gaps filled with hydrocarbon oil. (15th January 2015) - Maradia, U; Hollenstein, Ch; Wegener, K
Abstract: In order to understand the role of electrode materials in electrical discharges with micro gaps (<200  µ m) filled with a liquid hydrocarbon dielectric, the post-breakdown phase of low ignition voltage (100 V) and low current (<20 A) pulsed electric discharges is experimentally investigated. The electric discharge energies are selected in the range from 1 to 150 mJ. Due to the non-repetitive and transient nature of the micro-discharges, time-resolved imaging, spectroscopy and electrical analysis of single discharges are performed. The plasma–material interaction is investigated by analysing the erosion craters on anode and cathode. It is found that the electrode materials in these multiphase discharges affect the gas bubble dynamics, the transport properties of the discharge plasmas and the transition from the gaseous to metallic vapour plasma. The change in the energy fractions dissipated in the electrodes in function of the discharge time is influenced by the thermo-physical properties of the electrode materials. The simulation of craters in multiple discharge process requires consideration of the gas bubble dynamics due to different energy fractions and plasma flushing efficiencies.